1991
DOI: 10.1093/infdis/163.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Saliva and Blood for Human Immunodeficiency Virus Prevalence Testing

Abstract: Testing saliva for the detection of human immunodeficiency virus (HIV) antibodies has many potential advantages for epidemiologic surveillance. A commercial ELISA kit and a standardized in-house immunoblot (IB) system were slightly modified to enhance antibody detection in saliva. Frozen saliva specimens from Toronto Sexual Contact Study participants (including sequential saliva specimens collected during seroconversion) were tested as were fresh saliva samples collected from a population of street-based intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 8 publications
1
41
1
Order By: Relevance
“…The use of oral fluid, which is a mixture of gingival crevicular fluid and saliva secretion, has been suggested as an alternative to serum antibody testing for HIV [Archibald et al, 1986;Cao et al, 1989;Crofts et al, 1991;Major et al, 1991], HAV [Stuart et al, 1992;Parry et al, 1989], and HBV [Ben-Aryeh et al, 1985], and shows promise. Although the salivary glands secretion contains mostly IgA, the crevicular fluid probably represents transudate of plasma, where IgM and IgG are predominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of oral fluid, which is a mixture of gingival crevicular fluid and saliva secretion, has been suggested as an alternative to serum antibody testing for HIV [Archibald et al, 1986;Cao et al, 1989;Crofts et al, 1991;Major et al, 1991], HAV [Stuart et al, 1992;Parry et al, 1989], and HBV [Ben-Aryeh et al, 1985], and shows promise. Although the salivary glands secretion contains mostly IgA, the crevicular fluid probably represents transudate of plasma, where IgM and IgG are predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that antibodies to various viral infections can be detected not only in serum but also in other body fluids [Parry et al, 1987]. A correlation between serum antibodies and salivary or urinary antibodies has been reported in some viral infections, e.g., human immunodeficiency virus (HIV) [Archibald et al, 1986;Cao et al, 1989;Major et al, 1991;Crofts et al, 1991;Desai et al, 1991], hepatitis A virus (HAV) [Stuart et al, 1992;Parry et al, 1989], rubella [Saleh, 1991] and following immunization against polio virus [Zaman et al, 1991], rota virus [Ward et al, 1992;Friedman et al, 1993], and HAV [Hurni et al, 1993;Laufer et al, 1995]. As for HCV, oral fluid [Thieme et al, 1992;Sherman et al, 1994] and urine obtained from autopsy cases [Zhang et al, 1994] were suggested as alternative specimens for serum, for serodiagnosis of infection with this agent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, large numbers of samples can be collected simultaneously from groups (17). As a noninvasive and painless method, oral fluid collection may be more acceptable compared to phlebotomy and offers a potential for a higher degree of collection compliance among subjects being tested for surveillance purposes, thereby reducing sampling bias (38). Individuals such as children, IV drug users, and obese people whose blood may be difficult to obtain can be easily sampled.…”
Section: Discussionmentioning
confidence: 99%
“…It is suitable for pharmacodynamic studies of complex interactions of drugs at their sites of action in intact living tissue, and it leaves endogenous metabolic and oxygenation pathways, as well as synaptic functions, largely intact. 4 , 7 In vivo microdialysis allows the direct assessment of endogenous substances and is used in PD studies alongside, or instead of, other sampling techniques, such as equilibrium dialysis, 8 ultrafi ltration sampling, 9-12 saliva sampling, [13][14][15] and skin blister fl uid sampling. 14 , 16 It has become an increasingly popular and powerful technique to determine extracellular concentrations of glucose, lactate, glycerol, hormones, and various neurotransmitters and/or their metabolites.…”
Section: Introductionmentioning
confidence: 99%